ANALISIS LOGAM TIMBAL (Pb) PADA PENSIL ALIS YANG BEREDAR DI KABUPATEN TULUNGAGUNG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Rosyidah, Semi; Harmastuti, Nuraini; Rejeki, Endang Sri (Jurnal Farmasi & Sains Indonesia, 2024)
Eyebrow pencil is a cosmetic that is used to correct less symmetrical eyebrows. The colors marketed are very diverse. Lead is also obtained from tools used during the production process. This study aims to determine the lead content in eyebrow pencils and to determine the lead levels in eyebrow pencils circulating in Tulungagung by atomic absorption spectrophotometry (AAS) still meets the requirements of BPOM No. 12 of 2019. Sampling using a purposive sampling technique. Preparation samples were carried out using the dry deconstruction method. The research began with chemical and physical qualitative analysis. The determination of lead levels using AAS at a wavelength of 283.3 nm was then determined. The AAS analytical method is suitable for lead based on the results of method verification meeting the requirements including linearity with a value of r = 0.9929, accuracy of 102%, LOD 0,1189 mg/L, but did not meet the LOQ of 0.3964 mg/L. The results showed that 3 out of 5 samples were positive for lead with levels ranging from 4.9339-5.4896 mg/kg. The results still meet the BPOM contamination limit requirements, which are not more than 20 mg/kg, thus all samples are still within safe limits according to the requirements set by BPOM.